Analysis and Solutions of Silent Heart Attack Using Python - Sharma, Bhuvan; Kaur, Spinder (International Journal of Computer Sciences and Engineering, 2022)
We live in the twenty-first century, which is full of computers and electrical technologies that make human existence simpler. Artificial intelligence and machine learning are crucial in making life simpler for humans. In contrast, several ailments have evolved as a result of making life simpler, one of which is silent heart attack. Although there are medical treatments for this condition, there are only a few approaches that can forecast the silent heart. We can create models that can predict and detect heart attacks using artificial intelligence and machine learning. Some analysis has been done in this research while working on the road of predicting and detecting heart disease. Artificial neural network techniques are applied. Age , sex , cholesterol are some of the parameters that are set to predict silent heart attack.